(untitled) (Emancipação, 2024)
The history of the National Movement of the Population in Street Situation (MNPR) in Brazil has been marked by struggle and resistance since the 1990s. Comprised of individuals who have lived or are currently homeless along with their supporters, this movement aims to address the issues faced by the population in street situations in the country. The objective of this study was to explore the relationship between MNPR and public policies targeted at this population. Data from published studies and emerging findings from primary research focused on the meanings attributed by workers in the Unified Social Assistance System were employed. The analysis was conducted using the methodology proposed by Spink (2013), focusing on the production of meanings. The results, on the one hand, identify difficulties that mark the performance of public services in dealing with the street reality, and on the other hand, highlight the production of prejudiced meanings about a population that remains on the margins of society. This underscores the importance of social cohesion through a representative social movement.